Designing Closed-Ended Questions into Open-Ended Questions to Support Student’s Creative Thinking Skills and Mathematical Communication Skills - Septiani, Syilvia; Retnawati, Heri; Arliani, Elly (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The ability of creative thinking and mathematical communication is important in learning mathematics. However, in fact mathematics learning in schools today has not shown an optimal effort to help students develop creative thinking skills and mathematical communication skills. The purpose of this study is to examine the use of open-ended questions in mathematics learning and in the evaluation of mathematics learning to support the ability of creative thinking and mathematical communication skills of students, this will be implemented in the perspective of literature review. The type of research used is a systematic and structured literature review, where researchers synthesize relevant study results from international and national literature through Google Scholar, Eric, DOAJ, Scopus and ScienceDirect. Based on the analysis results obtained that mathematical learning using open-ended questions is effectively used to support the ability of creative thinking and mathematical communication skills of students; the provision of open-ended questions can be familiarized with providing learning methods leading to an open-ended approach; the test in the form of open-ended questions can be used as a tool to measure the ability of creative thinking and mathematical communication skills of students; the use of open-ended question can be applied to all levels of education; and the need for high creativity from teachers to prepare learning by applying open-ended questions.